2020
DOI: 10.1142/s0129065720500562
|View full text |Cite
|
Sign up to set email alerts
|

A Swallowing Decoder Based on Deep Transfer Learning: AlexNet Classification of the Intracranial Electrocorticogram

Abstract: To realize a brain–machine interface to assist swallowing, neural signal decoding is indispensable. Eight participants with temporal-lobe intracranial electrode implants for epilepsy were asked to swallow during electrocorticogram (ECoG) recording. Raw ECoG signals or certain frequency bands of the ECoG power were converted into images whose vertical axis was electrode number and whose horizontal axis was time in milliseconds, which were used as training data. These data were classified with four labels (Rest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Some studies regarding the above neural oscillations were investigated for clinical applications. The lowerfrequency neural oscillations in the sensorimotor cortex measured by scalp electroencephalogram (EEG) were used for decoding in rehabilitation using brain-machine interface techniques (Ramos-Murguialday et al, 2013;Shindo et al, 2011), whereas HG activities could be used to decode more accurate, rather than lower, frequency bands (Hashimoto et al, 2020a;Yanagisawa et al, 2011Yanagisawa et al, , 2012a. PAC could be used to detect or predict epileptic seizures (Amiri et al, 2019;Edakawa et al, 2016).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Some studies regarding the above neural oscillations were investigated for clinical applications. The lowerfrequency neural oscillations in the sensorimotor cortex measured by scalp electroencephalogram (EEG) were used for decoding in rehabilitation using brain-machine interface techniques (Ramos-Murguialday et al, 2013;Shindo et al, 2011), whereas HG activities could be used to decode more accurate, rather than lower, frequency bands (Hashimoto et al, 2020a;Yanagisawa et al, 2011Yanagisawa et al, , 2012a. PAC could be used to detect or predict epileptic seizures (Amiri et al, 2019;Edakawa et al, 2016).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…High γ activity is a key oscillation that reflects the neural processing of sensory, motor, and cognitive events 23–25 . High γ activities also show better functional localization than that in lower frequency bands 23 and have come to be known as useful features for decoding neural signals 12 . Here, we hypothesized that the analysis of high γ activities acquired by ECoG measurements would be able to reveal swallowing‐related cerebral oscillation changes in the order of milliseconds that have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…11 Next, we demonstrated that deep transfer learning applied to intracranial electroencephalogram (EEG) signals was able to classify swallowing intention well. 12 Current neuromodulation strategies for dysphagia stimulate brain areas or peripheral organs regardless of patients' swallowing intention. We hypothesized that if the stimulation was executed by the patients' swallowing intention, a higher degree of recovery would be obtained by sensory neurofeedback.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations